Effects of auxin and ethylene on root growth adaptation to different ambient temperatures in Arabidopsis. (April 2019) - Fei, Qionghui; Zhang, Jiahe; Zhang, Zheru; Wang, Yuxiang; Liang, Liyuan; Wu, Lei; Gao, Huanhuan; Sun, Yingli; Niu, Bingtao; Li, Xiaofeng
Highlights: The root growth of most TAA1 loss-of-function mutants is more sensitive to higher temperatures. Root elongation in ckrc1-1 is less sensitive to lower temperatures and more sensitive to higher temperatures than that of Col-0. The response pattern and interaction of the auxin and ethylene to the ambient temperature change is complex. Abstract: As sessile organisms, plants can modify their growth strategy in response to different temperatures, however very little is known about how roots growth responds to ambient temperature change. Here, we found that high temperature-induced root elongation is dependent on light intensity and the root growth of most TAA1 loss-of-function mutants is more sensitive to higher temperatures in Arabidopsis . TAA1 encodes a tryptophan aminotransferase which involved in the indole-3-pyruvic acid (IPA) pathway of indole-3-acetic acid (IAA) biosynthesis. The root elongation in ckrc1-1 (one allele mutant of TAA1 ) is less sensitive to lower temperatures and more sensitive to higher temperatures than that of Col-0. By comparing the regulatory mechanisms of ckrc1-1 root growth at different temperatures (17 °C, 22 °C, and 27 °C), different interactions between signals (auxin and ethylene) and the effects of downstream genes were observed at different ambient temperatures in Arabidopsis . Lower temperature-enhanced ETR1 -mediated ethylene signaling did not promote the expression of CKRC1, while higher temperature-enhanced signaling did. CKRC1 had an important role in the ACC inhibition of cell elongation at 22 °C and 27 °C but not at 17 °C. CKRC1 -dependent auxin biosynthesis was critical for maintaining PIN1, PIN2, and AUX1 expression at lower temperatures. CKRC1, AUX1, and PIN2 regulated root elongation by affecting different regions of the root at different temperatures in Arabidopsis . Our experimental results suggested that changes in the in vivo signals at different temperatures were multi-layered in Arabidopsis .